(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Positional inaccuracy is a major public engineering problem, and the cause of errors which lead to inaccurate measurements. The main challenge faced by many researchers is the accuracy. Hence, this paper involved comparing various map projections and datums effect on accuracy using 7 parameter method and root mean square errors (RMSE) test. In order to prepare data for analysis, sets of points in the study area, which is located in north of Iraq in Sulaymaniyah Governorate (Arbat City), were selected as follows: first set of ten checkpoints (reference points) was selected randomly. The cartographic parameters for these points were (Lat. /Long. coordinates) and datum was WGS84 using Differential GPS. Then other sets of points were ten Ground Control Points (GCP) for the same positions, but in this case were Cartesian coordinates with different projections and datums. The idea was to convert coordinates system of the second set points to geographic coordinate system for all specified projections using 7 parameter method. After that calculate RMSE between transformed coordinates and original coordinates (first set of checkpoints). The projection and datum that will guarantee less RMSE will be the best for study area. In this method required acquire ground control points (GCP) and global position system points (GPS points), for the purpose completing the study all the needed coordinates were measured using DGPS. Not only datum transformation from global datum (WGS1984-UTM-Zone-38N) to local datum (Karbala1979-UTM-Zone-38N) were performed, but also producing new maps for the purpose of comparisons. The results demonstrated that UTM projection and local datum (Karbala1979-UTM-Zone-38N) were the best for study area according to RMSE test.